Effect of single dose alcohol administration on malondialdehyde, glutathione,total protein and hydroxproline levels of rat liver - , Sibel DİNÇER and , Eser ÖZ and , Seren ÖZENİRLER (Turkish Journal of Gastroenterology 1, 2019)
-